2016
DOI: 10.1371/journal.pntd.0005122
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibitor of Nuclear Export (SINE) Compounds Alter New World Alphavirus Capsid Localization and Reduce Viral Replication in Mammalian Cells

Abstract: The capsid structural protein of the New World alphavirus, Venezuelan equine encephalitis virus (VEEV), interacts with the host nuclear transport proteins importin α/β1 and CRM1. Novel selective inhibitor of nuclear export (SINE) compounds, KPT-185, KPT-335 (verdinexor), and KPT-350, target the host’s primary nuclear export protein, CRM1, in a manner similar to the archetypical inhibitor Leptomycin B. One major limitation of Leptomycin B is its irreversible binding to CRM1; which SINE compounds alleviate becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 66 publications
(84 reference statements)
1
48
0
Order By: Relevance
“…We have previously shown that RSV replication is negatively affected by XPO1-mediated nuclear transport inhibition using LMB at nanomolar concentrations (15). Targeting XPO1 with KPT-335 has also proven effective both in vitro and in vivo against several strains of the influenza virus (26,27) and against the Venezuelan equine encephalitis virus (VEEV) in vitro (28). siRNAs were used to inhibit expression of XPO1 in A549 cells, followed by infection with RSV A2, and this was associated with substantial reduction in RSV replication in human epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that RSV replication is negatively affected by XPO1-mediated nuclear transport inhibition using LMB at nanomolar concentrations (15). Targeting XPO1 with KPT-335 has also proven effective both in vitro and in vivo against several strains of the influenza virus (26,27) and against the Venezuelan equine encephalitis virus (VEEV) in vitro (28). siRNAs were used to inhibit expression of XPO1 in A549 cells, followed by infection with RSV A2, and this was associated with substantial reduction in RSV replication in human epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, KPT-335 inhibited nuclear export of the vRNP, resulting in reduced influenza virus replication and decreased disease pathogenesis (26,27). KPT-335 has also proven effective against Venezuelan equine encephalitis virus (VEEV) in vitro by inhibiting the nuclear export of the capsid protein (28). In a previous study conducted as a randomized, double-blind, placebo-controlled, dose-escalating phase 1 clinical trial in healthy human volunteers, KPT-335 was found to be generally safe and well tolerated, with adverse events occurring in similar numbers and grades as placebo (ClinicalTrials.gov registration number NCT02431364).…”
mentioning
confidence: 99%
“…Compounds that indirectly interfere with VEEV replication by modifying intracellular processes in the host were also investigated as potential therapeutic options to modulate the course of alphavirus infections (17)(18)(19)(20). These included (i) an inhibitor of glycogen synthase kinase-3␤ (GSK-3␤) that governs proinflammatory responses in the host cell (17); (ii) acriflavine, an inhibitor of Ago2 (18); (iii) D-(Ϫ) enantiomer of carbodine, which inhibited cellular CTP synthetase and was capable of decreasing the levels of intracellular CTP (19); (iv) VX-497, a reversible uncompetitive inhibitor of inosine-5=-monophosphate dehydrogenase, that demonstrated a moderately negative effect on VEEV replication in vitro (20); and (v) selective inhibitors of nuclear export, which enhanced accumulation of the capsid protein in cell nuclei and thus decreased the titers of released VEEV (21). Ribavirin, a broad-spectrum antiviral drug, exhibited a very limited effect against VEEV even if applied at concentrations higher than 500 M (20).…”
mentioning
confidence: 99%
“…VEEV-TC83 viral stocks were produced from electroporation of in vitro transcribed viral RNA generated from the pTC83 plasmid [a kind gift from Ilya Frolov, The University of Texas Medical Branch at Galveston] as described (22). All experiments were performed under BSL-2 conditions.…”
Section: Viruses Body Fluids and Nt Particlesmentioning
confidence: 99%